Optimizing Social Media for Doplang Tourism Village Empowerment - Senowarsito Senowarsito*; Yuli Kurniati Werdiningsih; Ibnu Fatkhu Royana; Andi Priyolistiyanto (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The various problems experienced by Doplang Village are the lack of competence and capacity of managers in developing local potential and the absence of involvement of all elements for the role of communities in the advancement of tourist villages.. Another problem is the not optimal use of sosial media in the development of tourist villages. The resolution presented by the team is the competence and capacity of managers in developing lokal potential to support the creation of a tourist village. The various solutions offered will be realized in the form of comprehensive outreach, training, mentoring, monitoring and evaluation in order to obtain optimal results. For this reason, the Sosial Media Optimization program for Empowering Tourism Villages in Doplang needs to be implemented immediately in order to increase the competence and capacity of youth. This program is more focused on empowering the lokal potential of Doplang Village through facilitation and capacitation of Karang Taruna in Doplang Village. The outcome of this endeavor is a rise in the capacity of youth organizations; the pioneering Doplang tourist village managed by Karang Taruna.